One-step method for the synthesis of aryl olefins from aryl aldehydes and aliphatic aldehydes - Borate, Hanumant B.; Gaikwad, Supriya H.; Kudale, Ananada S.; Chavan, Subhash P.; Pharande, Shrikant G.; Wagh, Vitthal D.; Sawant, Vikram S. (Tetrahedron Letters, 2013)
A conceptually new one-step reaction affording unexpected aryl olefinic product from aromatic aldehyde, aliphatic aldehyde and malononitrile in the presence of acetic acid-ammonium acetate under mild reaction conditions without using any metal catalyst is reported. This novel reaction was used to prepare a number of substituted aryl olefins including new molecules. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Aliphatic aldehyde; Aromatic aldehyde; Aryl olefin; Dicyanoaniline; Malononitrile